Refinement strategy for antivenom preparation of high yield and quality. - Tihana Kurtović; Maja Lang Balija; Marija Brgles; Dora Sviben; Monika Tunjić; Hrvoje Cajner; Martina Marchetti-Deschmann; Günter Allmaier; Beata Halassy (Public Library of Science (PLoS), 2019)
Antivenoms from hyperimmune animal plasma are the only specific pharmaceuticals against snakebites. The improvement of downstream processing strategies is of great interest, not only in terms of purity profile, but also from yield-to-cost perspective and rational use of plasma of animal origin. We report on development of an efficient refinement strategy for F(ab')2-based antivenom preparation. Process design was driven by the imperative to keep the active principle constantly in solution as a precautionary measure to preserve stability of its conformation (precipitation of active principle or its adsorption to chromatographic stationary phase has been completely avoided). IgG was extracted from hyperimmune horse plasma by 2% (V/V) caprylic acid, depleted from traces of precipitating agent and digested by pepsin. Balance between incomplete IgG fraction breakdown, F(ab')2 over-digestion and loss of the active principle's protective efficacy was achieved by adjusting pepsin to substrate ratio at the value of 4:300 (w/w), setting pH to 3.2 and incubation period to 1.5 h. Final polishing was accomplished by a combination of diafiltration and flow-through chromatography. Developed manufacturing strategy gave 100% pure and aggregate-free F(ab')2 preparation, as shown by size-exclusion HPLC and confirmed by MS/MS. The overall yield of 75% or higher compares favorably to others so far reported. This optimised procedure looks also promising for large-scale production of therapeutic antivenoms, since high yield of the active drug and fulfillment of the regulatory demand considering purity was achieved. The recovery of the active substance was precisely determined in each purification step enabling accurate estimation of the process cost-effectiveness.